Transcriptomic Basis of Metamorphic Competence in the Salt-Marsh-Dwelling Polychaete Capitella teleta. - Burns, Robert.; Pechenik, Jan A. (Tufts University. Tisch Library., 2018)
Marine invertebrate larvae typically take hours to weeks after being released into the plankton before becoming "competent" to metamorphose. The mechanisms that govern this transition between the precompetent and metamorphically competent states are unknown. We studied gene expression patterns in precompetent and competent larvae of the salt-marsh-dwelling polychaete worm Capitella teleta (Blake, Grassle & Eckelbarger, 2009)—a species in which precompetent larvae are unusually easy to distinguish from competent larvae—to determine differences in gene expression associated with the onset of metamorphic competence. More than 1530 genes were more highly expressed in precompetent larvae, while more than 1060 genes were more highly expressed in competent larvae. Competent larvae downregulated the expression of genes belonging to gene ontologies relating to growth and development and upregulated those associated with ligand-binding transmembrane channels with possible chemo- and mechanosensory functions. Most of these channels were annotated as being from the degenerin/epithelial sodium channel family or the G-protein-coupled receptor family; proteins from these families can have chemosensory functions. Serotonin and GABA (γ-aminobutyric acid) receptors are among the genes that were upregulated in competent larvae; both have been shown to induce larvae of C. teleta and other marine invertebrates to metamorphose and are thought to be components of the signal transduction pathway that leads to metamorphosis. Overall, it appears that once larvae of C. teleta have completed development of the internal structures and physiology required for juvenile life during the precompetent period, they then upregulate the expression of chemosensory proteins and neurotransmitter receptors that will enable them to detect and transduce a settlement cue signal.